2015
DOI: 10.1186/s12885-015-1810-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiles of pilocytic astrocytoma are related to their three different locations, but not to radiological tumor features

Abstract: BackgroundPilocytic astrocytoma is the most common type of brain tumor in the pediatric population, with a generally favorable prognosis, although recurrences or leptomeningeal dissemination are sometimes also observed. For tumors originating in the supra-or infratentorial location, a different molecular background was suggested, but plausible correlations between the transcriptional profile and radiological features and/or clinical course are still undefined. The purpose of this study was to identify gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…In particular, Jeyapalan et al [ 20 ] identified an intergenic CpG site associated to IRX2 that resulted to be differentially methylated between the two tumor groups; whereas we detected a differential methylation of a CpG island that spans the promoter region and part of the gene body of IRX2 . In our sample set, IRX2 gene showed a hypermethylation and an expected downregulation in supratentorial PAs compared to the infratentorial PAs (Figure 4A ), confirming the gene expression profile observed by the other studies [ 16 , 18 , 20 ]. The expression level of this gene was in line with that observed in the normal tissues (Figure 4B and Figure 4C ), suggesting that its downregulation is probably more of a reflection of where the tumor develops rather than the onset of PA per se .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In particular, Jeyapalan et al [ 20 ] identified an intergenic CpG site associated to IRX2 that resulted to be differentially methylated between the two tumor groups; whereas we detected a differential methylation of a CpG island that spans the promoter region and part of the gene body of IRX2 . In our sample set, IRX2 gene showed a hypermethylation and an expected downregulation in supratentorial PAs compared to the infratentorial PAs (Figure 4A ), confirming the gene expression profile observed by the other studies [ 16 , 18 , 20 ]. The expression level of this gene was in line with that observed in the normal tissues (Figure 4B and Figure 4C ), suggesting that its downregulation is probably more of a reflection of where the tumor develops rather than the onset of PA per se .…”
Section: Discussionsupporting
confidence: 89%
“…The differentially expressed genes identified by Sharma and colleagues [ 16 ] are implicated in the development of the forebrain and the hindbrain. One of these genes, IRX2 , was found differentially expressed [ 16 , 18 , 20 ] and differentially methylated between infratentorial and supratentorial PAs in our and other studies [ 5 , 20 ]. In particular, Jeyapalan et al [ 20 ] identified an intergenic CpG site associated to IRX2 that resulted to be differentially methylated between the two tumor groups; whereas we detected a differential methylation of a CpG island that spans the promoter region and part of the gene body of IRX2 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This left eight genes to be analyzed (Ascl1, Irx2, Irx5, Klf15, Meis1, Msx2, Pax3, and Pbx3). In order to validate these genes, an independent dataset of gene expression from pilocytic astrocytoma tumors was interrogated [45]. All eight of these genes were reported to be overexpressed in infratentorial as compared to supratentorial tumors in this independent dataset, validating these findings.…”
Section: Neural Development Related Genes Overexpressed In Infratentomentioning
confidence: 54%
“…To explore the expression level of RAF1 mRNA in the PA specimen in comparison with other PA expression profiles, we examined two large online available datasets containing HG-U133_Plus_2 expression array data from 47 (E-GEOD-73066) and 49 (E-GEOD-44971) PA patients, respectively (15,16). RAF1 was not differentially expressed (data not shown), indicating that activation of Raf-1, rather than its overexpression, is the cancer driver event in the patient.…”
Section: Resultsmentioning
confidence: 99%